Challenges and treatment options for rheumatoid arthritis during pregnancy. (23rd July 2016) - Gerosa, Maria; Schioppo, Tommaso; Meroni, Pier Luigi
ABSTRACT: Introduction : Rheumatoid arthritis (RA) can spontaneously improve during pregnancy. However, a considerable proportion of patients can experience a flare and high disease activity has been associated with an increased risk of adverse pregnancy outcome. Thus, the treatment of RA in pregnant women should be selected taking into account both the potential harmful effects of the treatment and the risk associated with discontinuation. Areas covered : Recent publications regarding safety of the most important disease modifying anti-rheumatic drugs (DMARDs) during pregnancy has been reviewed. A systematic literature search of MEDLINE was conducted using pregnancy, teratogenicity, adverse effects, embryo/foetal-toxicity as key search terms for each DMARD. Expert opinion : A great body of evidence suggest that hydroxychloroquine, sulfasalazine, and non-fluorinated steroids can be continued throughout pregnancy, while methotrexate and leflunomide should be discontinued 3 months before pregnancy. Continuation of TNFi during the first part of pregnancy should be considered when benefits outweigh the potential risk of teratogenicity. Data regarding other biologics are scant and, at present, they should be stopped before pregnancy.